Creativity in Language Learning: How language teachers view creative teaching practices - Henriksen, Ásta (Menntavísindasvið Háskóla Íslands, 2020)
Being creative is an integral part of being a human. Most people recognise the feeling of joy after engaging in a creative activity and creativity is a force that drives human evolution. Therefore, it is interesting that creativity is one of the six fundamental pillars defined in the national curriculum, which education in upper secondary schools in Iceland is to rest on. It is not hard for language teachers to facilitate creativity in the classroom. Language learning opens doors to endless possibilities since teachers can choose diverse topics and twine them together with any teaching method they like.The aim of this study was to find out whether nine language teachers in upper secondary schools see reasons to give their students opportunities to be creative and if they do, why. Also, to find out which teaching methods they use and, finally, whether they face any obstacles that prevent them from using creative teaching methods. Creativity is discussed in regard to the ideas presented in the National Curriculum Guide and the report of the National Advisory Committee on Creative and Cultural Education, All our futures: Creativity, culture and education. The subject is also considered in the light of the scholars John Dewey, Lev Vygotsky, Elliot Eisner and Mihaly Csikszentmihalyi. Furthermore, the characteristics of a creative person, a creative learning environment and teaching methods which can foster students´creativity are discussed.This study is part of the research Upper Secondary School Practices in Iceland and is based on seven interviews and seven classroom observations from that research. Additionally, the researcher conducted four more interviews and made two more field studies. The participants come from eight different upper secondary schools in Iceland.The main findings show that most of the teachers find it important to foster their students´ creativity. Although very few examples were seen of creative work during field studies, the participants give various reasons for the importance of creative ...